2001
DOI: 10.1054/bjoc.2001.1729
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clodronate and antioestrogens on bone loss associated with oestrogen withdrawal in postmenopausal women with breast cancer

Abstract: SummaryIn this study we report bone mineral density (BMD) changes during clodronate and antioestrogen treatment in women with breast cancer having discontinued hormone replacement therapy (HRT) at the time of operation compared to women who had not used HRT immediately before the operation. 61 postmenopausal women with operable breast cancer were treated with the adjuvant antioestrogen tamoxifen 20 mg or toremifene 60 mg daily for 3 years. All patients were randomized to clodronate (1.6 g daily orally) or cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Comparative studies have shown that both toremifene and tamoxifen prevent reductions in BMD in the lumbar spine and proximal femur, and that these effects are reflected by changes in a wide range of bone biochemistry markers such as pyridinoline, deoxypyridinoline and urinary cross-linked aminoterminal telopeptide of type Ⅰ collagen [53][54][55] . Toremifene and tamoxifen have also been used successfully in combination with the bisphosphonate clodronate, with no significant differences between them [56,57] . Some beneficial effects on BMD have been observed in premenopausal women at high risk for developing breast cancer taking toremifene 60 mg as chemoprevention, therefore making an attractive alternative to tamoxifen.…”
Section: Bone Mineral Density In Breast Cancer Patientsmentioning
confidence: 99%
“…Comparative studies have shown that both toremifene and tamoxifen prevent reductions in BMD in the lumbar spine and proximal femur, and that these effects are reflected by changes in a wide range of bone biochemistry markers such as pyridinoline, deoxypyridinoline and urinary cross-linked aminoterminal telopeptide of type Ⅰ collagen [53][54][55] . Toremifene and tamoxifen have also been used successfully in combination with the bisphosphonate clodronate, with no significant differences between them [56,57] . Some beneficial effects on BMD have been observed in premenopausal women at high risk for developing breast cancer taking toremifene 60 mg as chemoprevention, therefore making an attractive alternative to tamoxifen.…”
Section: Bone Mineral Density In Breast Cancer Patientsmentioning
confidence: 99%
“…In our experience, by contrast, the inferiority of toremifene was the product of 0.54% mean reduction from baseline in the toremifene-treated patients compared with 3.32% increase in BMD in the placebo group. The mean BMD response with placebo during the first year of our investigation compares favourably with the response to various forms of osteoporosis therapy in postmenopausal women [11,12], including some experiences with combination HRT [13,14] and raloxifene [15]. A marked placebo response, rather than a substantive decline in BMD with toremifene, is thus the major factor contributing to the overall statistical difference.…”
Section: Discussionmentioning
confidence: 66%
“…Statistical testing of the revised primary endpoints used an analysis of variance model with the effects: treatment group (placebo vs. toremifene); country (UK vs. Finland); time (12,24,36 and 60 months), and menopausal status (pre-versus postmenopausal). Interactions for treatment group by time, treatment group by menopausal status, and treatment group by menopausal status and time were also examined.…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence now suggests that treatment with bisphosphonates prevents AIBL [2,22,46,[60][61][62][63][64][65]. Because of the increased bone loss associated with the use of AIs, three international randomized studies, the Zometa-Femara Adjuvant Synergy Trials [Z-FAST, ZO-FAST, and E-ZO-FAST] were performed to evaluate the bone protective effects of bisphosphonates during endocrine treatment with letrozole.…”
Section: Letrozolementioning
confidence: 99%